Black Box Testing Dengan Teknik State Transition Testing Pada Inventori Alat-Alat Medis - Setiawan, Alvin; Gunawan, Heru; Hidayatullah, Alfin; Putra, Muhammad Aprinaldi Syah; Sugema, Rizqy Cahya; Pane, Aldo Hasiolan; Nasution, Ahmat Rajalli; Irsyad, Muhamad (CV. Information Technology Training Center - Indonesia (ITTC), 2022)
South Tangerang General Hospital has an inventory system for medical devices that are used for recording incoming and outgoing medical devices. By the Ministry of Health of the Republic of Indonesia 2018, hospitals need a service system that can meet the requirements for quality, safety, and benefits of maintaining the quality of medical devices and health supplies. To determine the quality of a system, it is necessary to test the software to see the conditions directly. Black Box Testing is one of the most commonly used testing methods. This method is done by looking at the input and output of each system flow. Testers in this test method do not have to understand the flow of system code but must know the flow of system expectations. One technique of the black box testing method is the state transition technique. The state transition technique is done by looking at the suitability of the flow from one path to the next. The results of testing on the medical equipment inventory system at South Tangerang General Hospital were found to be 100% appropriate.